Exploration of Leadership Competencies in College Athletes: An Impact of Student-Athlete Advisory Committee on Leadership Development - Karina Jolly; Alison Fridley; Jake Simms; Chris Corr; Sarah Stokowski (Journal of Applied Sports Management, 2026)
The Student-Athlete Advisory Committee (SAAC) is designed to engage college athletes in decision-making processes that influence the NCAA and its member institutions. College athletes provide personal insight into the NCAA intercollegiate athletic experience, thereby influencing policy. SAAC participation prompts the application of transferable sport-specific skills such as leadership and work ethic in a professional setting. This study explores SAAC’s impact on the leadership competencies of college athletes. Results reveal that college athletes who participate in SAAC scored higher on three of the nine leadership factors examined. These findings highlight the importance of leadership programming tailored for college athletes, with SAAC emerging as a promising initiative within every athletic department. Consequently, both practical and theoretical implications emphasize the need for structured leadership initiatives to prepare college athletes for post-sport endeavors.
Keywords: NCAA; leadership; college athletes; professional development